2001
DOI: 10.1093/ptj/81.9.1534
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Functional Therapy Program on Motor Abilities of Children With Cerebral Palsy

Abstract: The groups' improvements in basic gross motor abilities, as measured by the GMFM in a standardized environment, did not differ. When examining functional skills in daily situations, as measured by the PEDI, children in the functional physical therapy group improved more than children in the reference group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
288
2
32

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 396 publications
(327 citation statements)
references
References 14 publications
5
288
2
32
Order By: Relevance
“…When the caregiver did not stimulate the child to use his/her abilities in social function and self-care, they became more dependent than the mildly impaired children, regardless of their similar behavior. Thus, the caregiver acts as an environmental factor of negative effect, limiting the child's potential, and it is crucial that the caregiver's assistance be limited to those situations where it is indispensable 13,[19][20][21][22][23][24][25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…When the caregiver did not stimulate the child to use his/her abilities in social function and self-care, they became more dependent than the mildly impaired children, regardless of their similar behavior. Thus, the caregiver acts as an environmental factor of negative effect, limiting the child's potential, and it is crucial that the caregiver's assistance be limited to those situations where it is indispensable 13,[19][20][21][22][23][24][25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…Different functional therapy approaches, based on theories of motor control and learning, have evolved within this framework. These approaches do not rule out training in segregated settings adapted for training acitivities, but commonly advocate that habilitation should take place in the ordinary enviroment of the child [3][4][5]. Goals should be set in collaboration with the child and family and accomplishment of tasks should be reached by identifying resources and changing constraints in the child, task, or the environment [5][6][7].…”
Section: Intensive Group Trainingmentioning
confidence: 99%
“…These approaches do not rule out training in segregated settings adapted for training acitivities, but commonly advocate that habilitation should take place in the ordinary enviroment of the child [3][4][5]. Goals should be set in collaboration with the child and family and accomplishment of tasks should be reached by identifying resources and changing constraints in the child, task, or the environment [5][6][7].Within the Swedish child and youth habilitation intensive group training (IGT) is offered to children with Cerebral Palsy (CP) and their parents. IGT is pursued in segregated contexts and is considered to be a complement to interventions done in the ordinary life environment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8 The underlying assumption is that a higher level of gross motor capacity leads to a higher level of capability and performance. 9 Several cross-sectional studies have investigated the relationship between gross motor capacity and daily-life mobility in children with CP. 7,[10][11][12] These studies found highly diverse relationships, ranging from weak to very strong.…”
mentioning
confidence: 99%